IMPLIKASI MANAJEMEN BIMBINGAN DAN KONSELING DI LEMBAGA PENDIDIKAN - afnibar afnibar (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2007)
It is knew how poor the counselor education employes performance Counselorgettig negative label by head master, by other teachers, and also by studentswhich them underhonourable They called as counselor police, whith unknown job discription: like cathing trouble maker students, collecting absent form, etc. This paper purpose the solution through implementing the guidance and counseling management in order to increase school cnnselor performance